Complementary Roles of Short and Long Pentraxins in the Complement-Mediated Immune Response to Aspergillus fumigatus Infections - Parente, Raffaella; Possetti, Valentina; Erreni, Marco; D’Autilia, Francesca; Bottazzi, Barbara; Garlanda, Cecilia; Mantovani, Alberto; Inforzato, Antonio; Doni, Andrea (Frontiers in Immunology, 2021)
The ubiquitous mold Aspergillus fumigatus is the major etiologic agent of invasive aspergillosis, a life-threatening infection amongst immune compromised individuals. An increasing body of evidence indicates that effective disposal of A. fumigatus requires the coordinate action of both cellular and humoral components of the innate immune system. Early recognition of the fungal pathogen, in particular, is mediated by a set of diverse soluble pattern recognition molecules (PRMs) that act as “ancestral antibodies” inasmuch as they are endowed with opsonic, pro-phagocytic and killing properties. Pivotal is, in this respect, the contribution of the complement system, which functionally cooperates with cell-borne pattern recognition receptors (PRRs) and other soluble PRMs, including pentraxins. Indeed, complement and pentraxins form an integrated system with crosstalk, synergism, and regulation, which stands as a paradigm of the interplay between PRMs in the mounting and orchestration of antifungal immunity. Following upon our past experience with the long pentraxin PTX3, a well-established immune effector in the host response to A. fumigatus, we recently reported that this fungal pathogen is targeted in vitro and in vivo by the short pentraxin Serum Amyloid P component (SAP) too. Similar to PTX3, SAP promotes phagocytosis and disposal of the fungal pathogen via complement-dependent pathways. However, the two proteins exploit different mechanisms of complement activation and receptor-mediated phagocytosis, which further extends complexity and integration of the complement-pentraxin crosstalk in the immune response to A. fumigatus. Here we revisit this crosstalk in light of the emerging roles of SAP as a novel PRM with antifungal activity.